2019
DOI: 10.1590/s2175-97902019000118224
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of the alcoholic leaves extract of Reinwardtia indica

Abstract: The present study aimed to evaluate the safety of the alcoholic leaves extract of Reinwardtia indica in Charles foster rats through an acute and sub-acute oral administration.For assessment of acute oral toxicity test, ratswere orally treated with single dose of the alcoholic leaves extract of Reinwardtia indica at the doses of 50, 250, 500, 1000 2000 and 5000 mg/kg. In sub-acute toxicity study, using the OECD guidelines no. 407, the extract was administered at the doses of 50, 250, 500, 1000, 2000 mg/kg/day f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Medicinal plants are good candidates for the health care system as herbal medicines against diseases perpetrating human beings and animals' husbandry. Concurrently, their worth sources are attested beyond doubts in recent years whereby many researchers have paid more attention to the exploitation of the herbal medicines for the development of antimicrobial products [37][38][39]. However, little is done to carry out toxicity evaluation of such herbal medicines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants are good candidates for the health care system as herbal medicines against diseases perpetrating human beings and animals' husbandry. Concurrently, their worth sources are attested beyond doubts in recent years whereby many researchers have paid more attention to the exploitation of the herbal medicines for the development of antimicrobial products [37][38][39]. However, little is done to carry out toxicity evaluation of such herbal medicines.…”
Section: Resultsmentioning
confidence: 99%
“…Each group was housed in an independent plastic cage for conducting treatments. Animal doses were modified from previous studies from Upadhyay and colleagues [38]. The TV-R, ME doses of 600, 1200 and 2000 mg/kg were used to treat groups 1, 2, and 3, respectively.…”
Section: Sub-acute Toxicity Assay: Groups Of Animals and Treatmentmentioning
confidence: 99%
“…In 1976, Goodpasture and Arrighi found that turmeric caused a dose and time-dependent induction of chromosome aberrations in several mammalian cell lines; these alterations were observed at concentrations of 10 μg/ml (Goodpasture & Arrighi, 1976). Curcumin can also induce DNA damage and chromosomal alterations both in vitro and in vivo (Sakano & Kawanishi, 2002;Urbina-Cano et al, 2006). For instance, curcumin concentrations of 2.5 and 5 μg/ml were shown to induce DNA damage to both the mitochondrial and nuclear genomes in cells (Cao, Jia, Zhou, Liu, & Zhong, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…& A. Fern (Anacardiaceae) (roots). Alcoholic leaves extract of Reinwardtia indica Dumort (Linaceae) was found nontoxic in single drug dose administration up to 5,000 mg/kg (acute study) and in sub‐acute administration up to 2,000 mg/kg (Upadhyay, Shukla, Tiwari, Dubey, & Mishra, 2019). Njugi (2018) reported Cleistanthus collinus (Roxb.)…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the day, the remaining food and water were collected, weighed to extrapolate the amounts of food and water that had been consumed by the animals during that day. The measuring unit for feeding was g/day, while the water consumption was measured in ml/day [ 44 ].…”
Section: Methodsmentioning
confidence: 99%